The Effect of Computer-Based Test (CBT) Utilization, Digital Literacy, and Internet Access on Grade V Students’ Science and Social Studies (SASS) Learning Outcomes - Syamsul Huda; K Kadeni; Ajar Dirgantoro; Imam Sukwatus Suja'i (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to analyze the effects of Computer-Based Test (CBT) utilization, digital literacy, and internet access on Grade V students’ Science and Social Studies (SASS) learning outcomes in public elementary schools in Ngunut District during the 2025/2026 academic year, both partially and simultaneously. The study employed a quantitative approach with an explanatory ex-post facto design. The population consisted of 587 students, and 233 respondents were selected using proportional random sampling with a 5% margin of error (Slovin formula). Data were collected through a 39-item Likert-scale questionnaire and documentation of students’ SASS achievement scores. Multiple linear regression analysis was conducted after fulfilling classical assumption tests, including normality, multicollinearity, heteroscedasticity, and linearity. The findings indicate that CBT utilization (β = 0.173; p = 0.018) and digital literacy (β = 0.432; p < 0.001) have positive and significant effects on learning outcomes, with digital literacy identified as the most dominant predictor. Internet access (β = 0.114; p = 0.176) does not have a significant partial effect. However, simultaneously, the three independent variables significantly influence learning outcomes (F = 58.871; p < 0.001). The coefficient of determination (R² = 0.435) shows that 43.5% of the variance in learning outcomes is explained by the model. These findings highlight that digital literacy competence is a key determinant in optimizing technology-based learning in primary education.